The major stages in the development of a regional centre. The case of Pécs (Hungary) - Horeczki, Réka (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2022)
The aim of the study is to provide an overview of the main milestones in the development of a regional centre in Hungary. Pécs is a centre of a depressed region. The Transdanubian region is among the 20 most disadvantaged regions of the European Union which shows a significant decline compared to previous years. This justifies the need for professional research directed at changing this situation by performing some tangible efforts. Pécs is a 2,000-years old city, acquiring various historical and mutually reinforcing central functions, by virtue of which it has developed into a regional centre. Of the historical drivers of the development of Pécs, the study is able to identify three groups of factors 1) centrality within its region, the regional functions it has fulfilled throughout its history, 2) culture and multiculturalism, and 3) industrial development. This study will analyse the relation of the cultural centre position and the other function of Pécs. The study is the first descriptive result of a research project1 that reviews the development and governance characteristics of a typical case of peripheral regions. Ongoing empirical analysis will allow the development of a development policy concept.